THE CONCEPT OF EXISTENTIALISM, ITS CHARACTERISTICS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the socio-philosophical views on Existence: the idea that a person remains at his own discretion, that only he decides what to do and is responsible for his actions, and that each person's existence is unique.